Reator enzimático de membrana para proteólise de soro de queijo, visando à produção de concentrado protéico com baixo teor de fenilalanina - Padilla, Rebeca Yndira Cabrera (Universidade Federal de São Carlos, 2007)
Enzymatic hydrolyzed proteins present some advantages over the pool of amino acids obtained after a chemical hydrolysis: lower osmolality (easier absorption by the organism) and better sensorial characteristics. The removal of phenylalanine (Phe) from these hydrolysates allows their use in the diet of phenylktonuria (PKU) patients. This Thesis studies the sequential hydrolysis of cheese whey proteins. This process aims at producing a protein hydrolysate with low contents of Phe, after two reaction stages: in the first one, concentrated cheese whey proteins are hydrolyzed by the endoprotease chymotrypsin, immobilized on agarose gel. The substrate of the second stage is the product of the first one. This reaction is the central focus of this Thesis, and consists in a hydrolysis using the exoprotease carboxipeptidase A (CPA), immobilized on the same matrix. Since the scope of this work was a process for obtaining a protein hydrolysate with low contents of Phe for phenylketonurics, another stage had to be incorporated: ultrafiltration, to separate the amino acids released by the action of CPA, mainly Phe (and other amino acids that inhibit the reaction). With this purpose, an enzymatic membrane reactor (EMR) is proposed. It should be noticed that, to the best of our knowledge, the reactor design presented here has not been published yet. The EMR had spherical agarose particles within the reaction space, retained by a stainless steel mesh (400 Tyler). Hence, the ultrafiltration membrane was in charge only of the separation of the amino acids in the hydrolysate, which was continuously recycled to the flask containing the immobilized enzyme. Assays to characterize the membranes were performed. These membranes were then used in the integrated process (reaction with immobilized enzyme coupled to the ultrafiltration), for different experimental conditions. The substrates where Prato and Minas Frescal cheese whey. Two set-ups of the ultrafiltration unit were tested: flat plate and hollow fiber, both with 1 kDa cut-off. The reactor volume/membrane area ratios were 7.5×10-2 cm and 76.9×10-2 cm, respectively. Finally, the performance of three systems was compared: EMR with flat plane and hollow fiber and a batch reactor, followed by diafiltration. The hollow fiber EMR showed the best performance (85% conversion, productivity of 275.2×10-7 ghidrolisado/mgPhe/UH-PHE/h and only 1% retention of Phe in the membrane, after assays of 10 h). The resulting product was appropriate for phenylketonurics, with high protein contents (53.4 g/L), mainly constituted by small peptides (≤ 5.8 kDa) and with 19.9 mgPhe/gProteína, within the admissible range for PKU
Keywords: Proteólise; Soro de queijo; Quimotripsina; Carboxipeptidase A; Reator enzimático de membrana; Concentrado protéico; Fenilcetonúricos; ENGENHARIAS::ENGENHARIA QUIMICA